GAMBARAN PENGETAHUAN IBU TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK DOWN SYNDROME DI SLB-B-C-D-AUTIS AZ-ZAKIYAH KOTA BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2020)
A down syndrome child have abnormalities of chromosome number 21. So the genetic information is to be interrupted and children are also experiencing irregularities physical and lead to have limitations in caring for the health of teeth and mouth. Therefore children with down syndrome need more attention from the mother to assist maintain the oral health of children. This study aims to determine the level of knowledge of mothers based on the characteristics of age, education and mother's work against the maintenance of oral health in down syndrome child in SLB-B-C-D-Autistic Az Zakiyah city of Bandung. Type of descriptive research, the technique of sampling used was accidental sampling. The results of the research in general shows that 66,6% of respondents included sufficient criteria, and 33.4% of the criteria is less, mother's knowledge level based on educational characteristics shows that most respondents (83.3%) belong to the old age group with the most knowledge level criteria that is sufficient, the level of mother's knowledge based on educational characteristics shows that most (83.3%) have a history of tertiary education with the highest level of knowledge criteria is sufficient and the level of knowledge of mothers based on the characteristics of work shows that on average (50%) the work of mothers is housewives with the most knowledge level criteria that is sufficient. Keywords : knowledge maintenance of dental and oral health, down syndrome.